The effectiveness of healthy behavior education on sleep quality in pregnant women with sleep disorder - Maryam Darvish; Mohammad Reza Zarbakhsh (Babol University of Medical Sciences, 2016)
Background: sleep quality disorder accounts for high rampancy among pregnant women, especially in the third trimester of pregnanc. Present study was conducted to assess effectiveness of behavioral-based treatment in improving sleep quality of pregnant women in the third trimester of pregnancy. Methods: this study is of experimental type with two-group pretest/posttest design conducted in 2014 on pregnant women in the third trimester of their pregnancy in the targeted health centers from among the existing health centers in Tarome city. All of these women completed the Pittsburg Sleep Quality Index (PSQI) following which they were divided in to two experimental and control groups. The experimental group was exposed to behavioral training (i.e. muscle relaxation and systematic desensitization) for one month, 2 times a week (8 sessions in total) for improvement of their sleep quality. The members of both groups, in the posttest, once again answered the research questionnaires. The obtained data were analyzed using multivariate analysis of covariance (MANCOVA) in the SPSS environment. The significance level was set at 0.01. Results: the behavioral interventions method, i.e. muscle relaxation and systematic desensitization, significantly improved sleep quality of the pregnant women in the experimental group, as compared with those in the control group. Conclusion: disturbance in sleep quality is one of the most prevalent psychological problems observed among pregnant women in the third trimester of pregnancy, hence behavioral interventions and training is suggested to be considered as a drug-free, low cost, and very suitable method for improvement of sleep quality.